Ecuador’s Zone 3 and the Social and Economic Factors that Impede Its Growth - Morales Molina, Tania; Ximena Morales-Urrutia; Geri Belén Bucheli-Vásquez; Alejandro Chaviano-Quesada (My University, 2024)
The popular and solidarity economy has become a promising alternative in the economic and social context of Ecuador. This model seeks to overcome the limitations of the traditional profit-centered approach and foster a more inclusive and sustainable development, through ventures focused on equity, community participation and solidarity, as well as employment generation and poverty reduction through the active participation of entrepreneurs and the local community (Maldonado et al. 2017).
Keywords: Economic; Entrepreneurship; Factors; Popular; Social; Solidarity